APLIKASI MOBILE LEARNING UNTUK PEMBELAJARAN BAHASA INGGRIS DI JURUSAN BIMBINGAN DAN KONSELING UNIVERSITAS NEGERI MEDAN - Albert Pauli Sirait (JGK (Jurnal Guru Kita), 2022)
Mobile Learning For English Subject In The Department Of Guidance And Counseling Universitas Negeri Medan. The purpose of this study was to determine the shape of the android based Mobile Learning needed by students majoring in guidance and counseling Unimed on learning English. This research has been conducted using ADDIE development model. Media experts give excellent ratings for throughout the all item of Media assessment. This application is tested on 30 students of the 1st half of Guidance and Counseling Department of the Faculty of Education Unimed. The results of calculations throughout the student questionnaire responses obtained 87.15%% percentage of aspects of good feelings, 86.57% of the student's interest aspects of the use of the application, 85.85% of aspects of attention, and 88.24% of aspects of student involvement.